Konseling tentang Diabetes Melitus Gestasional dan Pemeriksaan Glukosa di Puskesmas Tanralili - Nur Ismi Wahyuni; Ekayanti Ekayanti (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2021)
Gestational diabetes mellitus (GDM) is a glucose tolerance disorder that was first discovered during pregnancy which had never been diagnosed with diabetes in the mother and then showed high glucose levels during pregnancy. Women with GDM almost never give complaints even though the incidence of GDM can be threatening and very dangerous because it can cause several complications during pregnancy, childbirth and after childbirth is also one of the causes in cases of maternal and infant mortality. Pregnancy accompanied by diabetes is also at risk of causing maternal death up to 4 times 2. One other prevention that can be done is more intensive counseling and counseling from officers to all pregnant women about the description of the incidence of DMG. This activity was carried out at the Tanralili Public Health Center with the method of individual counseling to pregnant women in turn with brochures distributed to each pregnant woman, after which they took blood/glucose checks while. This activity was attended by 2 lecturers and 2 midwifery students as well as 20 pregnant women. This community service provides good benefits, namely getting knowledge about Gestational Diabetes Mellitus and being able to know glucose levels in the blood as screening so that it can prevent and detect early complications that will occur.